PENGGUNAAN NAVIGASI BINTANG DI ALAM BEBAS PADA MALAM HARI DALAM PENENTUAN ARAH KIBLAT - Samsudin samsudin; Ubaidillah Ubaidillah; Masriah Masriah (Mahkamah : Jurnal Kajian Hukum Islam, 2019)
AbstractIn conditions in the wild we often have difficulty in determining the direction, especially if we do not carry a pointing device such as a compass, therefore the position of heavenly bodies can be relied upon. The existence of celestial objects can be a navigation instrument that becomes a reference in determining the direction of the Qibla by observing the position of the star, this study was conducted to prove whether the position of a star can be used as a natural tool other than the sun in determining the Qibla direction.This study aims to answer the questions that formulate the problem: "How to use star navigation in determining the direction of Qibla in the wild and includes the results of the accuracy of the calculations and observations". This study uses qualitative research, data collected by means of interviews (interviews), observation, documentation and then analyzed by descriptive analysis method.The results of this study: the method of determining the direction of the Qibla by looking at the direction of the star in a particular month and time can be a reference to facing the Qibla direction accurately. To get these results, you can use regulus stars in the Leo constellation in April to May with calculations using the formula:WK = (X / 15) + (21˚ 32 '59.24 ") - (0˚ 03' 56.55" x date)) + KWD (for April).WK = (X / 15) + (19˚ 34 '42.56 ") - (0˚ 03' 56.55" x date)) + KWD (for May).In addition to using the above formula, getting accurate results is used as well as trial observations using a special compass tool to determine the Qibla direction. In this case, from April to May the location of the wild becomes a strategic place to determine the direction of the Qibla using regulus stars at a certain time. So wherever there is no reason for prayer not facing the Qibla direction.